Synthesis and Characterization of Mn(II), Co(II), Ni(II) and Cu(II) complexes with 4'-azachalcone and their adducts with 1,10-phenanthroline - N. H. Buttrus; R. Y. Dawod; I. A. Hassan (College of Education for Pure Sciences, 2006)
New complexes of general formula [M(L)2C12] , [M2(L)2C14] and adducts [M(L)2(phen)Cl2] ,where L=4'-azachalcone ,phen - 1,10-phenanthrolin, M=Mn(II),Co(Il),Ni(II) and Cu(II) have been prepared. The complexes and adducts were characterized by elemental analysis, conductivity measurements, magnetic moment and spectral (IR and electronic) studies. Magnetic moment values and electronic spectral data provide evidence for the existanee of tetrahedral environment around the metal ions in the complexes and octahedral geometry in the adducts.